Effect of media content and media use habits on aggressive behaviors in the adolescents - Akçay, Duygu; Akçay, Bülent Devrim (The European Research Journal, 2019)
Objective: This study aims to assess the effect of media content and media use habits on aggression in adolescents. Methods: This descriptive study was conducted between December 28, 2015 and January 7, 2016. The study sample consisted of 406 (66% male, 44% female, mean age: 15.16 ± 1.56 years) students who were registered in two schools in the provincial center of Konya, Turkey during the 2015-2016 academic year. Results: Surveyed aggression scores were higher in students who were frequently exposed to violent media (p < 0.001). The aggression scores were positively correlated with viewing television, DVDs, films/movies, playing computer/console games, using the Internet, listening to music, playing games on mobile phones, and total screen time and negatively correlated with participating in sports and reading newspapers and books. Conclusion: Health professionals should provide parents, educators, and children with information and advice on the attentive use of media and the negative health effects related to its uncontrolled use.